Addressing the challenge of customer management for SMEs - Alexandra Christopoulou; Panos Gialelis (SPOUDAI - Journal of Economics and Business, 2021)
Customer Management Softwares have become a critical strategy in business, since it became prominent that they improve a company's probability to achieve superior business results. Yet, for a company to be able to deliver superior portfolio management solutions, Technology, Data Analysis and Commercialization should smoothly work together. This study aims to create a solution that better serves the goals of SMEs while satisfying the end consumers' needs. SMEs in Greece and worldwide, due to lack in resources and access on the required expertise, are lacking significantly in the implementation of Customer Relationship Management technologies and Data Analysis in their operating model. As a result, they face a genuine competitive disadvantage in the race of knowing and effectively managing their customer base. As a preliminary stage, qualitative research was conducted through personal interviews with 30 SME managers from ten different market sectors, around their understanding and proper handling of data analytics, as well as the extent of the financial investment they are would be willing to make. At a following stage quantitative research was conducted to a representative sample of 600 residential area inhabitants utilizing the Computer Assisted Web Interview methodology. The research focused on identifying the consumers' expectations around the provision of personalized services and rewards through the capitalization of knowledge derived by loyalty programs. AmplifyTM Customer Management Platform was developed to help specifically SMEs to address the challenge of Customer Management, consolidating in one application the 3 fundamental pillars for database management that drives business results: customer data collection, customer analytics and personalized marketing, building upon SMEs existing resources, skillset and infrastructure.
Keywords: M31; 330; Customer management; SMEs innovation; customer retention; multi-channel marketing; marketing technology; personalization